Pengaruh Model Kooperatif Tipe Two Stay Two Stray Terhadap Hasil Belajar Matematika - Fikran Taslim; Halistin Halistin (IAIN Kendari, 2021)
This study was researched to determine the effect of the application of cooperative learning model type Two Stay Two Stray on improving students' math learning outcomes. The samples used were two of the six seventh graders in SMP there is Wangi-Wangi Selatan. This research was conducted in January-February 2020. This research is quantitative research with experimental research method using pseudo Quasi-Experimental Research. Data collection is done with pretest and posttest. Data processing is carried out using t-test and N-Gain test. Before data processing, homogeneity test and normality test are conducted. Hypothetical test results showed at the level of significance and obtained . This states that accepted and rejected. The results of the calculation of improved pretest study results of the experiment class have an average of 47.14 and posttest experiment classes have an average of 82.14 so that gained a gain of 0.662. The pretest kontrol class has an average of 47.14 and the Posttest kontrol class has an average of 65.71 so it gained a gain of 0.351. The conclusion is that the learning outcomes of both sample classes had significant differences and improved experimental class learning outcomes higher than the control class.Keywords : Math Learning Outcomes, Cooperative Learning, And Two Stay Two Stray